Boica Regon de la manta real - complejo turístico para la identidad histórica y nacional - Plan parcial circuito ambiental - Paipa (2019)
The development of the partial plan and the regional, sector and local action units suggested, start from the needs and regional problems previously analyzed. The urban approach is developed in order to meet those infrastructural, economic and social needs to generate a dynamism in the region that allows a macro connection with the country. The developed and proposed equipments are interconnected by means of nuclei and satellites that allow to be replicated in the region looking for innovative strategies that supply the exposed needs. The regional and sectoral SWOT analysis reflect the problems and the predominant needs of the sector. In general levels, the proposal is developed with the parameters and regulations studied and evaluated by the sector and the region. It is developed as a partial plan to generate a pattern of change in a main municipality, not only at the municipal level, but at general levels. where it is developed with economic, social and environmental levels in favor of the growth of the municipality and the region with the proposed master plan.